OPTIMASI MEDIA PRODUKSI METABOLIT ANTIBIOTIK DARI Bacillus tequilensis BSM-F SIMBIOSIS Halichondria panicea ASAL PERAIRAN CABBIYA MADURA - SHAFIRA AMALIA RAHMA, 051511133089 (2019)
Bacillus tequilensis BSM-F isolated from Halichondria panicea in Madura Cabbiya Water, Indonesia. The isolates were grown in Potato Dextrose Agar (PDA), Starch Casein Agar (SCA), Sabouraud Dextrose Agar (SDA), and Tryptic Soy Agar (TSA). It was found that the optimum media for Bacillus tequilensis BSM-F growth is SCA with 2,25 x 1013 CFU/mL. The media also used as media for producing antibiotic metabolic at 37 oC for five days against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. The solid fermentation method was used in the production of antibiotic activity, the antibiotic activity was measured every day by calculating the activity index. Inhibition zone appeared around the colony, and Bacillus tequilensis BSM-F in PDA showed the most optimum antibiotic activity with 1,98 ± 0,04 and 2,25 ± 0,03 in average activity index against Staphylococcus aureus ATCC 25923 and Escherichia coli 25922, respectively. Then, the concentration of PDA optimized at 0,25%;0,5%; and 1%. The result showed that the optimum media was reached at PDA 1% with 2,37 ± 0,06 and 2,68 ± 0,25 in average activity index against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922, respectively.